2004
DOI: 10.1099/jmm.0.45610-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Clostridium difficile variant toxinotypes and strains with binary toxin genes among clinical isolates in an American hospital

Abstract: Genetic variants of Clostridium difficile have been reported with increasing frequency, but their true incidence is unknown. C. difficile strains have been classified into variant toxinotypes according to variations in the pathogenicity locus encoding the major virulence factors, toxins A and B. Some strains produce an additional toxin, binary toxin CDT. This survey of clinical isolates (153) from patients in a single hospital set out to ascertain the distribution of variant toxinotypes and strains possessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 39 publications
1
93
2
4
Order By: Relevance
“…Among the serogroup A isolates, 16 were toxigenic (toxin A and B positive) and all were toxinotype 0. These results are in accordance with other studies that reported the high frequency of toxinotype 0 among clinical isolates (Geric et al, 2004). No isolate belonged to the hypertoxigenic toxinotype III recently described in North America (Loo et al, 2005).…”
Section: Resultssupporting
confidence: 83%
“…Among the serogroup A isolates, 16 were toxigenic (toxin A and B positive) and all were toxinotype 0. These results are in accordance with other studies that reported the high frequency of toxinotype 0 among clinical isolates (Geric et al, 2004). No isolate belonged to the hypertoxigenic toxinotype III recently described in North America (Loo et al, 2005).…”
Section: Resultssupporting
confidence: 83%
“…It has been recognized previously that the presence of functional binary toxin genes encoded by the 4.3 kb CDT locus correlates well with variant toxinotypes including A + B + , A 2 B + and A 2 B 2 strains (Stubbs et al, 2000;Rupnik et al, 2001Rupnik et al, , 2003aGeric et al, 2004;Spigaglia & Mastrantonio, 2002;Goncalves et al, 2004). This study presents an overview of all of the known variant toxinotypes and has confirmed that the full-length CDT locus is found in variant toxinotypes with significantly changed LCT toxin genes (shown in bold in Table 1), whereas the truncated version of the CDT locus is predominant in variant toxinotypes with minor changes in the LCT toxin genes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For toxinotypes IV, V, VI, IX, XIa, XIb and XII we tested one additional strain, for toxinotype III two additional strains and for toxinotype VIII seven additional strains. Three strains of toxinotype III were representatives of subtypes IIIa, IIIb and IIIc, which differed in B2s fragment RFLPs (Geric et al, 2004). Two representatives of the so far unpublished toxinotypes determined in this study (XXIII and XXIV) were also included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several intact mobile elements have also been identified within the PaLoc. Toxinotypes XIVa, Xb, XXII and IXc, all belonging to clade 2, possess a large 2000 bp IStron in tcdA (Geric et al, 2004;Mehlig et al, 2001), a type of mobile element first discovered in C. difficile (Hasselmayer et al, 2004b). The clade 3 PaLoc has a stably integrated transposon Tn6218 which does not interfere with toxin production .…”
Section: Other Lct Elementsmentioning
confidence: 99%